The performance of modified jatropha-based nanofluid during turning process - Talib, N.; S. Rao, N. R.; Jamaluddin, N. A.; Abdullah, H.; Saleh, A.; Lee, W. K.; Ahmad, S. (2021)
The industry's extensive use of petroleum-based metalworking fluid (MWF) harms the environment and humans. The production of bio-based MWF, especially from crude jatropha oil (CJO), has therefore taken numerous initiatives. This aimed to formulate newly modified jatropha oil (MJO) with the addition of 0.05wt.% hBN and 0.05wt.% MoS2 as the nanofluid for MWF. The performance of the nanofluids was determined through the turning process in terms of cutting temperature, workpiece surface roughness, tool life and tool wear of the tool lubricated by the nanofluids. The performance of the nanofluid samples was compared with the synthetic ester (SE). From the results, after conducted 100mm axial cutting length MJO+hBN+MoS2 recorded the lowest in cutting temperature and surface roughness compared to all samples. The result shows that MJO+hBN+MoS2 has longer tool life (6500mm) compared to SE (6000mm). Abrasion and adhesion were observed as the dominant tool wear mechanism. In conclusion, MJO+hBN+MoS2 shows better machining performance and has the potential to be an environmentally friendly metalworking fluid.